Study on the Acid⁃Catalyzed Cyclization Reaction of Allylbenzenes and Tetrazine - Wenqing LIU; He WANG; Xin WANG; Lei LI (Shiyou huagong gaodeng xuexiao xuebao, 2025)
Indeno[1,2⁃d]pyridazine derivatives have wide applications in pesticides,pharmaceuticals,and other fields due to their excellent biological activities.Therefore,the development of rapid and efficient synthetic methods for these compounds has attracted increasing attention from researchers.A novel acid⁃catalyzed cyclization reaction between allylbenzene and tetrazine was designed.Reaction intermediates were trapped,and their structures,along with those of the products,were characterized using nuclear magnetic resonance spectroscopy.The results indicate that the reaction proceeds through intermolecular [4+2] cycloaddition and intramolecular Friedel⁃Crafts alkylation processes,enabling one⁃step synthesis of indeno[1,2⁃d]pyridazine derivatives.The reaction also exhibits a broad substrate scope and good functional group compatibility,yielding a series of indeno[1,2⁃d]pyridazine derivatives with 67%~95% yields.In gram scale experiments,the target product was obtained with an 81% yield, demonstrating the potential practical value of this reaction.